Electrolyte‐Free Spectroscopy and Imaging of Graphite Intercalation. Issue 1 (10th December 2020) - Stark, Madeline S.; Cheng, Judy; Kim, Hailey; Kuntz, Kaci L.; Warren, Scott C.
Abstract: Engineering electrode materials for optoelectronic and energy storage applications requires a fundamental understanding of intercalation using spatially‐resolved techniques. However, spectroscopic methods can have limited spatial resolution and low intensity since the signal passes through electrolyte. Here, a device geometry is presented in which the electrolyte is laterally separated from the area probed spectroscopically, so that the signal does not pass through the electrolyte. This geometry enables us to visualize ion transport with optical microscopy and monitor charge transfer with Raman and visible reflectance spectroscopies. In addition, vibrational changes are probed in the mid‐IR, a region previously difficult to access due to electrolyte absorption. This geometry will allow many layered electrodes to be probed in situ using time‐ and spatially‐resolved techniques, including photon and electron spectroscopies. Abstract : Spectroscopic imaging of graphite electrodes in an electrolyte‐free environment is presented. A barrier laterally separates the electrolyte region from the area of graphite probed during intercalation. This feature enables in situ imaging and spectroscopy without electrolyte interference to reveal ion transport dynamics and vibrational features in battery electrodes with time‐ and spatially‐resolved techniques.